MULTIPLEX REAL-TIME PCR METHOD AS A RELIABLE TEST IN THE ROUTINE MICROBIOLOGY STUDY OF VAGINAL MICROBIOME IN WOMEN WITH GENITAL TRACT DISCHARGE - Radoslav Baykushev; Vessela Raykova (Peytchinski Publishing, 2024)
Untreated vaginal discharge is a risk factor for complications. Correct diagnosis is crucial. The purpose of this study was to apply Femoflor-16 to study the vaginal microbiome in women with genital tract discharge. Material/Methods: A total of 45 women were included in the study. Vaginal/cervical swab - one for routine tests and Gram staining and another for PCR Femoflor-16, were tested. Clinical diagnosis of bacterial vaginosis (BV) was done by using Amsel's criteria. Microbiologically, BV was assessed by applying a Nugent score system and Femoflor-16. Results: A total of 45 women with genital tract discharge were included in the study. Based on Amsel's clinical criteria, 9 (20%) of them were diagnosed with BV. Based on Nugent's score system, 11(24,4%) were categorized as having BV. Only 40 samples were compared, and the results were tested using Femoflor-16 and Nugent score system. Of them, 33 (83%) were in agreement as a result of using both methods. Femoflor-16 detected species such as aerobic bacteria (Enterobacteriасeae, Streptococcus spp., Staphylococcus spp.), Mycoplasma spp., Ureaplasma spp. and yeast-like microorganisms (Candida spp.). Conclusions: A reliable, comprehensive, and on-time diagnosis of BV is needed. Nucleic acid amplification tests nowadays complement the "classic" laboratory methods. The real time multiplex PCR test Femoflor-16 can be effectively used in vaginal microbiota evaluation in women with discharge. It can identify a wide range of microorganisms, including bacteria that are difficult to culture, normal Lactobacilli microflora and complex of aerobic and anaerobic microorganisms, mycoplasmas and Candida spp. In addition, it is able to determine the number and ratio of microorganisms in the total bacterial mass, which further orients to the disease state and the role of the microorganism as an opportunistic or obligate pathogen.